Concomitant ablation for non-paroxysmal atrial fibrillation: combined energy versus cryoablation alone - Tsaroev, Bashir; Sharifulin, Ravil; Afanasyev, Alexander; Khrushchev, Sergey; Murtazaliev, Murtazali; Lovtsova, Darya; Kashapov, Robert; Ruzankin, Pavel; Mustaev, Muslim; Bogachev-Prokophiev, Alexander (Frontiers in Cardiovascular Medicine, 2024)
Background Surgical ablation of atrial fibrillation has been the most efficient treatment for atrial fibrillation (AF). Combined energy (CE) ablation and cryoablation alone (CA) are the most common energy modes used for ablation, however, comparative data is lacking. Objectives To compare the efficacy of CE ablation with CA in the setting of concomitant biatrial ablation for non-paroxysmal AF. Methods A retrospective analysis of 453 patients with non-paroxysmal AF undergone concomitant biatrial ablation from November 2007 to December 2022 during elective cardiac surgery using either combined bipolar radiofrequency with cryoenergy or cryoenergy alone was performed. Propensity score matching was conducted to balance the covariates in the groups. Results There were 157 patients per group after matching. CE ablation was associated with lower odds of atrial tachyarrhythmia recurrence (OR = 0.13, 95% CI 0.02–0.91, p = 0.040), a significantly lower rate of hospital readmissions due to rhythm disruption (HR = 0.34, 95% CI 0.18–0.65, p < 0.001), and lower cumulative incidence of stroke (SHR = 0.38, 95% CI 0.15–0.97, p = 0.043). No significant difference in permanent pacemaker implantation was observed between the two groups. Conclusions In the setting of concomitant biatrial ablation for non-paroxysmal AF, combined bipolar radiofrequency and cryoablation appear to be a superior treatment modality compared to cryoablation alone in achieving long-term freedom from atrial arrhythmias, in reducing arrhythmia-related hospital readmissions and ischemic strokes.